Comparing the patient reported physical function outcome measures in a real‐life international cohort of patients with psoriatic arthritis - Leung, YY; Orbai, AM; de Wit, M; Balanescu, A; Dernis, E; Soubrier, M; Eder, L; Smolen, JS; Coates, LC; Gossec, L (Wiley, 2021)
Objectives We evaluated the psychometric properties of three patient‐reported outcomes (PROMs) to assess the physical function in psoriatic arthritis (PsA).